2019
DOI: 10.1039/c9nj01760g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient selective 4-aminophenol sensing and antibacterial activity of ternary Ag2O3·SnO2·Cr2O3 nanoparticles

Abstract: The electrochemical oxidation of 4-AP based on Ag2O3·SnO2·Cr2O3 NPs/binder/GCE sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…As binding agent, it was used the 5% nafion suspended in the ethanol, which was enhanced the binding strength between GCE and CdSe/ZnS QDs. Thus, the applied nafion was improved the binding strength in addition to increase the electron transport rate of the proposed electro-chemical sensor [72][73][74][75][76][77] . To test the proposed selectivity of chemical sensor, the number of environmental contaminants with the concentration of 0.1 µM and applied potential ranging from 0 to +1.5 V were investigated in phosphate buffer solution at neutral pH.…”
Section: Detection Of 3-cp By Electrochemical Approach the Proposed mentioning
confidence: 99%
“…As binding agent, it was used the 5% nafion suspended in the ethanol, which was enhanced the binding strength between GCE and CdSe/ZnS QDs. Thus, the applied nafion was improved the binding strength in addition to increase the electron transport rate of the proposed electro-chemical sensor [72][73][74][75][76][77] . To test the proposed selectivity of chemical sensor, the number of environmental contaminants with the concentration of 0.1 µM and applied potential ranging from 0 to +1.5 V were investigated in phosphate buffer solution at neutral pH.…”
Section: Detection Of 3-cp By Electrochemical Approach the Proposed mentioning
confidence: 99%
“…Finally, the study indicated that trimetallic oxide nanocomposites are promising candidates for photocatalytic applications and environmental protection due to their nanostructure formation and perturbations of electronic energy levels. 51,52,[60][61][62] Anti-bacterial activity of the Ag$NiMn 2 O 4 nanocomposite…”
Section: Kinetics Study Of Methyl Violet 6b Degradation By the Ag$nimmentioning
confidence: 99%
“…In summary, the self-assembled nanostructured material, Ag$NiMn 2 O 4 , is expected to be applied as an efficient antibacterial agent against MDR bacteria as well as an industrial sterilization system. 51,[60][61][62] Electrochemical analysis of the Ag$NiMn 2 O 4 nanomaterials/ binder/GCE Fabrication of GCE with Ag$NiMn 2 O 4 nanomaterials using Naon. The electrochemical response of the desired sensor is dependent on the precision of the fabrication of GCE with the Ag$NiMn 2 O 4 nanomaterial, and attention must be paid to the modication process of GCE.…”
Section: Kinetics Study Of Methyl Violet 6b Degradation By the Ag$nimmentioning
confidence: 99%
“…For photocatalytic applications, the location of the TiO 2 nanoparticle plays an important role in the photoactivity, since various nanoparticles should be accessible for both photons and reactive molecules. The advantages of using these materials as support for TiO 2 in relation to photocatalytic processes are addressed by comparing the photocatalytic activity of TiO 2 nanoparticles deposited by different routes with TiO 2 nanoparticles on mesoporous materials [1][2][3]. Three-dimensional nanostructures have interconnected networks of bulk materials and larger accessible surface areas with respect to their lower dimensional counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%